SYNCHRONOUS AND ASYNCHRONOUS WITH FLIPPED LEARNING ENVIRONMENT IN PRIMARY SCHOOL - Rindaningsih, Ida; Findawati, Yulian; Hastuti, Wiwik Dwi; Fahyuni, Eni Fariyatul (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2021)
The challenges of learning during the pandemic are currently a big task for the world of education. The unpreparedness of school institutions, students, and parents in facing changes in the distance learning system has an impact on the implementation of learning during the COVID-19 pandemic. For this reason, it is necessary to have a learning solution that can answer the challenges of learning using digital-based learning. This research aims to develop a model of the reverse learning environment. This development research examines various aspects of the needs of the student learning environment during the COVID-19 pandemic. The subjects of this study were school principals, deputy principals, and elementary school teachers who have implemented the 2013 Curriculum. The results of this study show that the synchronous and asynchronous framework with the reverse learning environment approach is proven valid and feasible applied to learningÂ COVID-19. The findings synchronous, and asynchronous that are implemented efficiently by the teacher, and applications will continue to be developed.